Relationship between observational learning and health belief with physical activity among adolescents girl in Isfahan, Iran - Rostamian, Marzieh (Iran J Nurs Midwifery Res, 2016)
BACKGROUND: Physical activities among adolescents affects health during pubescence and adolescence and decrease in physical activities among adolescents has become a global challenge. The aim of the present study was to define the relation between the level of physical activity among adolescent girls and their health beliefs as personal factor and level of observational learning as environmental factor. MATERIALS AND METHODS: The present study was a cross-sectional study that was conducted on 400 students aged from 11 to 19 years in Isfahan, Iran. Information regarding the duration of physical activity with moderate/severe intensity was measured in four dimensions of leisure time (exercising and hiking), daily activities, and transportation-related activities using the International Physical Activity questionnaire. Health belief structures included perceived sensitivity, intensity of perceived threat, perceived benefits, and barriers and self-efficacy; observational learning was measured using a researcher-made questionnaire. RESULTS: Results showed that perceived barriers, observational learning, and level of self-efficacy were related to the level of physical activity in all dimensions. In addition, the level of physical activity at leisure time, transportation, and total physical activity were dependent on the intensity of perceived threats (P < 0.05). CONCLUSIONS: This study showed that the intensity of perceived threats, perceived barriers and self-efficacy structures, and observational learning are some of the factors related to physical activity among adolescent girls, and it is possible that by focusing on improving these variables through interventional programs physical activity among adolescent girls can be improved.